The Phenomena of Envelope Beggars: Begging Education Begins From Using Envelope Media (Descriptive Study of the Night Market Kodam V Brawijaya Surabaya) - Hizbullah, Achmad (LPPM Universitas Jambi, 2024)
This research is motivated by the existence of begging education at the Kodam V Brawijaya night market, Surabaya City. Education that should be used as a means of escaping from poverty has turned into a means of a culture of poverty. Those beggars who are experienced have succeeded in exploiting children in their environment by using envelopes for begging. The purpose of this study is to reveal the true meaning of using envelopes as a medium for begging and how education should play an important role as a breaker of the culture of poverty in the city of Surabaya. This study uses qualitative methods with Alfred Schutz's phenomenological approach as a way to understand the interactions that occur between beggars and children, and how the field conditions support this. After carrying out the research stages, the researchers obtained the result that begging education and a culture of poverty would be overcome if families, communities and beggars had high concern for children and did not exploit them. Then the government must also contribute, namely by supporting the empowerment of the poor, adequate education, and meeting their needs evenly.